ზოგიერთი დეტალი გეორგიევსკის ტრაქტატთან დაკავშირებით - თაბუაშვილი, აპოლონ (ივანე ჯავახიშვილის სახელობის თბილისის სახელმწიფო უნივერსიტეტის გამომცემლობა, 2023)
Much has been written about the treaty of Georgievsk and numerous aspects concerning to this topic have been properly analyzed. Nevertheless, in our opinion, there are still some issues related to the treaty of Georgievsk that need further research. As we know, the final version of the agreement between the Russian Empire and the Kingdom of Kartli-Kakheti was approved by the Russian Emperor in February 1783, and it was presented to Erekle II in the middle of May of the same year. The king of Kartl-Kakheti delayed the process for about a month and a half. The fact was that it was during this period that the information was spread about the liquidation of the Crimean Khanate and its annexation by the Russian Empire. It seems that this fact made the king think a lot and put forward a new suggestion – he demanded to reflect the right of coronation of Georgian monarchs as kings in the agreement. Archival documents prove that in the letter sent at the end of June 1783, Erekle II requested an additional guarantee for safeguarding his kingdom. Pavel Potemkin, the commander-in-chief of the Caucasus Line, had no right to include it in the treaty without the emperor's permission. Hence, this issue was not reflected in the treaty. Due to this fact, Erekle II was clearly dissatisfied and sent his representative Sulkhan Tumanishvili to St. Petersburg immediately after the return of the Georgian delegation to his homeland. This time, Erekle categorically demanded to reflect the issue of coronation in the treaty. Finally, in September 1783, the Russian emperor approved demands of Erekle II. An additional article was written, according to which the Georgian monarchs were allowed to be crowned as king. According to above-mentioned article Erekle II received from the Russian government an even stronger guarantee of the protection of his kingdom based on the legitimate treaty. One of the demands put forward by Erekle II was the issue of Catholicos. As it is known, the independence of the Georgian Church was limited by the treaty of Georgievsk. In response to this, the king focused on the autocephaly of the Georgian Church and asked the Russian side to take this fact into account. In this regard, the activity of the Georgian king brought certain results. The another disputed issue was related to the territorial claims of the Georgian king. Erekle II claimed both the south-western Georgia conquered by the Ottomans and the neighboring khanates. On the other hand, the Russian Empire planned to take the khanates of the region under its protection and hoped for the help of the Georgian king in this matter. Even before the signing of the treaty, the Georgian side put forward a proposal that the territorial claims of Erekle II should be reflected in his titulature, although the Russian representatives did not meet this request at the time. In such conditions, even the Georgian king refrained from helping the Russians in Azerbaijan, for which Pavel Potemkin expressed his concerns towards the actions of the Georgians. Finally, a certain agreement was reached between the parties – the final version of the treaty included titulature of Erekle the way it was requested by the Georgian side. According to the above-mentioned titulature, Russia recognized Erekle's rights to the khanates of Yerevan, Ganja, Sheki and Shirvan, also Kaki (Sultanate of Elisu and Jar-Balakan) neighbouring Kartli-Kakheti Kingdom. At the same time, the king was announced as the heir of Samtskhe-Saatabago. On the other hand, the Georgian king sent his representatives to the khanates of Karabakh and Khoy and promised to act in favor of the interests of the Russian Empire. As for the form of address, according to the Treaty of Georgievsk, the Georgian king was referred to by the lower epithet. According to the Georgians, Erekle II was traditionally named as “Highness”, a more elevated epithet, hence they demanded the official establishment of the same epithet for their king. As a result, the Imperial court of Russia agreed to the above-mentioned request of the Georgians.
SOME DETAILS REGARDING THE TREATY OF GEORGIEVSK
https://geohistory.humanities.tsu.ge/ge/procedings/83-shromebi/178-shromebi-19.html